Feedback from bereaved relatives via Medical Examiners: what kinds of concerns are raised? - Saskie Dorman; Andy Brogan; Becky Protopsaltis; Ryan Barter (BMJ Open Quality)
Relatives can offer important insights into the quality of care. In England, the Medical Examiner (ME) system has been introduced to identify if there are any causes for concern relating to the cause of death or the person’s care in their final illness. We reviewed feedback from bereaved relatives to identify opportunities for improvement. Routinely collected data (date and place of death, demographics, relationship to the person who had died, concerns raised via the ME system) were collated over 12 months (March 2023 to February 2024, East Dorset, UK). Each comment recorded in the ME records was read by one of the authors and issues identified were coded as themes. Concerns were recorded in 8% and appreciative comments in 12%. The most frequent concerns raised related to family/carer communication (56% of concerns raised). Feedback also reported issues relating to access, delays and care which did not attend to what mattered. Effective feedback loops and meaningful action are important elements of generative governance.